Evaluation of Orchid-Like Aroma Between Different Grades of Taiping Houkui Tea by Solid-Phase Microextraction and Comprehensive Two-Dimensional Gas Chromatography Coupled with Time-of-Fight Mass Spectrometry. (20th April 2020) - Qi, Chen; Tianyang, Guo; Qiong, Wu; Jian, Yao; Renyi, Liao; Peng, Wu; Shaotong, Jiang; Yiyang, Dong
Abstract: Background: Taiping houkui tea won the title of "the King of Green Tea" at the International Tea Exposition in 2004, which had an orchid fragrance but the material basis of the orchid fragrance had not been revealed yet. Objective: To investigate the material basis of the orchid fragrance and identify the quality grade of Taiping houkui tea. Methods: A method was developed for evaluating orchid-like aroma between different grades Taiping houkui tea by solid-phase micro extraction (SPME) and comprehensive two-dimensional gas chromatography coupled with time-of-fight mass spectrometry (GC×GC-TOFMS). The crushed tea sample in a 25 mL headspace bottle was incubated at 90°C for 10 min. Then the gaseous sample was extracted by SPME divinylbenzene/polydimethylsiloxane fiber for 50 min and thermally desorpted at 250°C for 2 min. Results: In total, 735 volatile compounds were determined by SPME- GC×GC-TOFMS and 15 compounds were related to orchid-like aroma. Conclusions: The high-quality Taiping houkui tea has the orchid fragrance and the low-grade one does not; thus orchid-like aroma can be used as a reference of grades of Taiping houkui tea. Highlights: Thirty different grades of Taiping houkui tea samples were compared and analyzed experimentally, and the results showed that the special aroma substances, which played a key role in grade discrimination of Taiping houkui tea, were found by the statistical method.